Analisis Berbagai Variabel yang Berpengaruh terhadap Kinerja Aparatur Pemerintah Desa di Kabupaten Buru - Labbase, Ilham (Jurnal Aplikasi Manajemen, 2011)
The research was conducted in Buru regency with a population of 650 people village government apparatus. Sampling is done using stratified sampling method and proportional sampling as much as 15 percent from 650 people to 98 respondents. The analytical method used is descriptive analysis to explain qualitatively the results of research and analysis of data inference is used to test the hypothesis that using multiple linear regression method. All the analysis and testing is performed using SPSSprogram. This study examined several variables which consist of variable discipline, motivation, leadership skills and work environment simultaneously influence the performance of government officials in the village of Buru district. Partially, the most influential variable is the motivation of working in the District of Buru. Accordingly, to improve the performance of village government personnel in Buru district needs to consider all the variables studied with priority on work motivation